PERCEPTION OF TEACHERS ABOUT SNS AND ITS USE IN MANAGEMENT EDUCATION IN PUNE CITY - Anwar Shaikh, Dr. Aftab; Shaikh, Mrs. Zarina (IJRDO - Journal of Business Management, 2016)
Social networks and the need to communicate are universal human conditions. A general assumption is that communication technologies help to increase and strengthen social ties. The networks are described as social, because they allow communication with friends and colleagues study and strengthen the ties between members of these networks in the space of the Internet. These sites and social forums are means of communication directly with others socially and in the media. They are playing a big and influential role decision-making at the events of the global world economically, politically, socially and educationally In the field of E-Learning, the social network sites handled the big problem raised by educators in the recent period. This paper attempts to briefly discuss the perception of teachers about Social networking sites and its use by management students